Manajemen Keuangan Lembaga Pendidikan Pondok Pesantren: Studi Kasus pada Pondok Pesantren Darunnajah Bakalan, Suruhan Kidul Kabupaten Tulungagung - Syifaul Maulidah, Dewi; Nuril Hidayati, Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and analyze the financial management applied to Darunnajah Islamic Boarding School Bakalan Suruhan Kidul. This research was conducted using a qualitative approach to the type of case study research. The results of the study show that Darunnajah Bakalan Suruhan Kidul Islamic Boarding School has carried out financial management, although it is still carried out in a simple way, but it has been carried out in accordance with financial management functions which include: 1) planning, 2) implementation and 3) evaluation or reporting. From the results of the analysis of the research conducted, it can be concluded that in the financial management of the Darunnajah Bakalan Suruhan Kidul Islamic Boarding School, budget planning is carried out in consultation with caregivers, ustaz and ustazah and the board of the Islamic boarding school at the beginning of each school year. Implementation of financial management is carried out based on predetermined plans. Evaluation or reporting is carried out at the end of the school year in the form of an accountability report which is then reported to caregivers and senior boarding school officials.